Uji Aktivitas Antiseptik Ekstrak Etanol Tanaman Bundung (Scirpus grossus L.) Terhadap Penyembuhan Luka Sayat pada Tikus Putih (Rattus norvegicus) - Amalia, Ghina Rezki; Saftia Aryzki; Darini Kurniawati (BORNEO JOURNAL OF PHARMASCIENTECH, 2024)
Bundung Plant (Scirpus grossus L.) is one of the wild plants that is very easy to get, but not many people know its properties. This plant is empirically used by the community as a wound treatment and antimicrobial. This plant is proven to contain several compounds such as tannins, flavonoids, phenolics, saponins, steroids and terpenoids. This study aims to determine the antiseptic activity of ethanol extract of Bundung Plant with various concentrations and the most effective concentration in healing white rat incision wounds (Rattus norvegicus). the method used begins with the extraction process, making extract concentrations, preparing test animals, dividing test animal groups, treating test animals, observing the healing phase and testing antiseptic activity. The results of the group test on the measurement of the average length and healing time of the incision wound, the wound that closed the fastest was the 4% extract group which was seen clinically could be distinguished by its healing speed, from the results of the analysis there was no significant difference in the healing time span and measurement of the average length of the incision wound. The conclusion of this study is that the ethanol extract of the Bundung Plant (Scirpus grossus L.) has antiseptic activity on the healing of incision wounds of white rats (Rattus norvegicus) which is observed through the healing time span and there is no significant difference in changes in wound healing time and the length of the incision wound in the five groups and the most optimal concentration of ethanol extract of the Bundung Plant (Scirpus grossus L.) with the concentration of the extract observed clinically is 4%.